Mesoporous Silica Based Nanostructures for Bone Tissue Regeneration - Ghosh, Sougata; Webster, Thomas J. (Frontiers in Materials, 2021)
Porous nano-scaffolds provide for better opportunities to restore, maintain, and improve functions of damaged tissues and organs by facilitating tissue regeneration. Various nanohybrids composed of mesoporous silica nanoparticles (MSNs) are being widely explored for tissue engineering. Since biological activity is enhanced by several orders of magnitude in multicomponent scaffolds, remarkable progress has been observed in this field, which has aimed to develop controlled synthesis of multifunctional MSNs with tuneable pore size, efficient delivering capacity of bioactive factors, as well as enhanced biocompatibility and biodegradability. In this review, we aim to provide a broad survey of the synthesis of multifunctional MSN based nanostructures with exotic shapes and sizes. Further, their promise as a novel nanomedicine is also elaborated with respect to their role in bone tissue engineering. Also, recent progress in surface modification and functionalization with various polymers like poly(L-lactic acid)/poly(ε-caprolactone), polylysine-modified polyethylenimine, poly(lactic-co-glycolic acid), and poly(citrate-siloxane) and biological polymers like alginate, chitosan, gelatin are also covered. Several attempts for conjugating drugs like dexamethasone and β–estradiol, antibiotics like vancomycin and levofloxacin, and imaging agents like fluorescein isothiocyanate and gadolinium, on the surface modified MSNs are also covered. Finally, the scope of developing orthopaedic implants and potential trends in 3D bioprinting applications of MSNs are also discussed. Hence, MSNs based nanomaterials may serve as improved candidate biotemplates or scaffolds for numerous bone tissue engineering, drug delivery and imaging applications deserving our full attention now.